1966
DOI: 10.1901/jeab.1966.9-659
|View full text |Cite
|
Sign up to set email alerts
|

STIMULUS ASPECTS OF AVERSIVE CONTROLS: LONG TERM EFFECTS OF SUPPRESSION PROCEDURES1

Abstract: Five years ago, pigeons trained to peck a key for food were periodically presented with a 1000 cps tone which ended with electrical shock. They were then tested for the stimulus generalization of conditioned suppression. After an interruption of 2.5 yr, another series of generalization tests showed no loss of suppression. The present study was conducted 1.5 yr later to retest the effect of an extended interruption on retention of suppression. It was found, again, that suppression did not decline over time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…There was no retention decrement in the overall level of suppression when all nine rats were considered as a group; this agrees with earlier reports (Gleitman and Holmes, 1967);Hoffman et al, 1963;Hoffman et al, 1966), but there was a marked change in the pattern of responding during the CS interval.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There was no retention decrement in the overall level of suppression when all nine rats were considered as a group; this agrees with earlier reports (Gleitman and Holmes, 1967);Hoffman et al, 1963;Hoffman et al, 1966), but there was a marked change in the pattern of responding during the CS interval.…”
Section: Discussionsupporting
confidence: 91%
“…This study demonstrated that forgetting can be observed with the conditioned suppression technique when attention is focused on the pattern of responding that reflects a temporal discrimination of shock occurrence. There was no retention decrement in the overall level of suppression when all nine rats were considered as a group; this agrees with earlier reports (Gleitman and Holmes, 1967);Hoffman et al, 1963;Hoffman et al, 1966), but there was a marked change in the pattern of responding during the CS interval.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could have made excitatory conditioning too weak to be remembered with the passage of time. The result is somewhat surprising, as conditioned suppression is usually not affected by retention intervals even larger than 90 days (e.g., Gleitman & Holmes, 1967;Hoffman, Selekman & Fleshler, 1966). Even when an inhibitory process is also involved (e.g., Hendersen, 1978), forgetting of fear excitation does not occur after retention intervals of 25 or 35 days.…”
mentioning
confidence: 97%
“…The fourth ratio that I will consider has a different denominator and the form: ( b − a )/ b . This ratio was used by Pfautz, Donegan, and Wagner (1978 ; see also Hoffman, Selekman, & Fleshler, 1966 ) in Pavlovian shock conditioning experiments with rats and rabbits. a and b refer, respectively, to the response rates (lever pressing or heart rate) during the conditioned stimulus and to the baseline rate.…”
Section: Four Discrimination Ratiosmentioning
confidence: 99%